2004
DOI: 10.1191/1352458504ms1091cr
|View full text |Cite
|
Sign up to set email alerts
|

Waldenström's macroglobulinemia developing in a patient with multiple sclerosis: coincidence or association?

Abstract: Multiple sclerosis (MS) has been reported in association with haematological abnormalities, including monoclonal gammopathies. We present a 54-year-old male patient with a 30-year history of MS who was admitted to our hospital for investigation of anaemia and increased erythrocyte sedimentation rate. A monoclonal IgM protein was detected by serum protein immunofixation, while bone marrow biopsy indicated a 70% infiltration by small lymphoplasmacytoid cells, in the context of a lymphoplasmacytoid immunocytoma, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…One report described MM that developed in a patient suffering from MS for 26 years [76] . Similarly, a case of Waldenstrom's macroglobulinemia was described in a patient suffering from MS for 39 years [77] . Conversely, MS and peripheral demyelinating neuropathies have been described in patients with monoclonal gammopathies [78] .…”
Section: Autoimmune Neurologic Disorders In Multiple Myelomamentioning
confidence: 90%
“…One report described MM that developed in a patient suffering from MS for 26 years [76] . Similarly, a case of Waldenstrom's macroglobulinemia was described in a patient suffering from MS for 39 years [77] . Conversely, MS and peripheral demyelinating neuropathies have been described in patients with monoclonal gammopathies [78] .…”
Section: Autoimmune Neurologic Disorders In Multiple Myelomamentioning
confidence: 90%
“…Previous studies have focused on the possible association between MS and CNS [19][20][21], bladder, breast [6], skin [22], hematological and lymphatic cancers [10,12,23] (Table 5). In the present study, the observed number of brain tumors, hematological, skin, lymphatic and digestive cancers did not exceed the expected number.…”
Section: Discussionmentioning
confidence: 99%
“…Whether the coexistence of these neurologic diseases and WM is coincidental or a result of common pathogenetic mechanisms remains to be answered. Several case reports document WM developing in patients with MS. 36,37 Conversely, there are reports of MS that developed in patients with monoclonal gammopathies. 38,39 This association between MS and WM could be explained by a shared genetic susceptibility or, possibly, a common immune abnormality.…”
Section: Autoimmune Neurologic Disordersmentioning
confidence: 97%
“…30 Furthermore, deposits of IgM were observed in the endoneurium of the damaged nerve fibers. 31 There are reports of myasthenia gravis, 32-34 amyotrophic lateral sclerosis, 29,35 and multiple sclerosis (MS) 36 in patients with WM. Whether the coexistence of these neurologic diseases and WM is coincidental or a result of common pathogenetic mechanisms remains to be answered.…”
Section: Autoimmune Neurologic Disordersmentioning
confidence: 98%